Factors Associated with Death in Patients with Melioidosis in Nongkhai Hospital - กราบไกรแก้ว, สุกัญญา (Journal of Health Science of Thailand, 2022)
The global incidence of melioidosis in 2016 was approximately 165,000 deaths per year, with a mortality rate of 89,000 per year (54.0 percent), while Thailand has a mortality rate of 2,800 per year (37.0 percent). From the information of Nongkhai Hospital during the year 2019-2021, it was found that melioidosis was the fifth most common cause of community-acquired infection with septicemia, accounting for 5.4-6.2%, and the mortality rate was as high as 6.7-10.8%. This descriptive study aimed to determine the factors associated with death in patients with melioidosis in Nongkhai Hospital from January 2016 to December 2020. Factors were analyzed using the Chi-square test, and only statistically significant factors were further analyzed by using multiple logistic regression (95% CI, p <0.05). A total of eligible 184 patients were divided into 43 deaths (23.4%) and 141 survivors (76.6%). The factors associated with death in patients with melioidosis included severe sepsis, shock, HCO3 <20 mmol/L, Cr >1.1 mg/dl, and treatment with a single intravenous antibiotic (p<0.05). In conclusion, combined intravenous and oral antibiotics should be considered in conjunction with the monitoring of patients with severe sepsis or septic shock, metabolic acidosis, and acute kidney injury in order to reduce the mortality rate from the disease.